Meal patterns across ten European countries – results from the European Prospective Investigation into Cancer and Nutrition (EPIC) calibration study. Issue 15 (19th May 2016) - Huseinovic, E; Winkvist, A; Slimani, N; Park, MK; Freisling, H; Boeing, H; Buckland, G; Schwingshackl, L; Weiderpass, E; Rostgaard-Hansen, AL; Tjønneland, A; Affret, A; et al.
Abstract: Objective: To characterize meal patterns across ten European countries participating in the European Prospective Investigation into Cancer and Nutrition (EPIC) calibration study. Design: Cross-sectional study utilizing dietary data collected through a standardized 24 h diet recall during 1995–2000. Eleven predefined intake occasions across a 24 h period were assessed during the interview. In the present descriptive report, meal patterns were analysed in terms of daily number of intake occasions, the proportion reporting each intake occasion and the energy contributions from each intake occasion. Setting: Twenty-seven centres across ten European countries. Subjects: Women (64 %) and men (36 %) aged 35–74 years ( n 36 020). Results: Pronounced differences in meal patterns emerged both across centres within the same country and across different countries, with a trend for fewer intake occasions per day in Mediterranean countries compared with central and northern Europe. Differences were also found for daily energy intake provided by lunch, with 38–43 % for women and 41–45 % for men within Mediterranean countries compared with 16–27 % for women and 20–26 % for men in central and northern European countries. Likewise, a south–north gradient was found for daily energy intake from snacks, with 13–20 % (women) and 10–17 % (men) in Mediterranean countries compared with 24–34 % (women) and 23–35 % (men) in central/northern Europe. Conclusions: We found distinct differences in meal patterns with marked diversity for intake frequency and lunch and snack consumption between Mediterranean and central/northern European countries. Monitoring of meal patterns across various cultures and populations could provide critical context to the research efforts to characterize relationships between dietary intake and health.